DEVADARU (CEDRUS DEODARA (ROXB.) LOUD.): A CRITICAL REVIEW ON THE MEDICINAL PLANT (International Journal of Ayurveda and Pharma Research, 2015)
Devadaru (Cedrus deodara) an important plant belongs to Pinaceae family found in the north-western Himalayas at altitude of 1200-3000 meter. The aromatic wood of this beautiful tree is used as carminative, anti inflammatory, diaphoretic, diuretics, antipyretic, antileprotic. In Caraka samhita it is one among the Satanya shodhana and Anuvasanopaga group of drugs and Sushruta also considered it as the Vata Shamana group, Katuvarga and Eladi group. It is the chief timber of north west India and is used for all purpose of construction of railway sleepers, bridges, and even for furniture and shingles. The oil obtained is used for mange in horses and sore feet in cattle. It is in use since vedic period in temples and in making incense even said that by sitting under its shade many diseases cures especially asthma. Here the present review study is an attempt to provide reported detail information of this herb from various Samhitas and its study in modern area like its phytoconstituents and pharmacological activities.